108k views
0 votes
(cosx-cos3x)/(sinx+sin3x)=tanx. How do I prove this?

1 Answer

1 vote

Answer:

Apply the trigonometric identities:


cos\alpha-cos\beta=-2sin(\alpha+\beta)/(2)*sin(\alpha-\beta)/(2)


sin\alpha+sin\beta=2sin(\alpha+\beta)/(2)*cos(\alpha-\beta)/(2)


sin(-\alpha)=-sin(\alpha)\\cos(-\alpha)=cos(\alpha)


(sin\alpha)/(cos\alpha)=tan\alpha

Explanation:

By definition you have:


cos\alpha-cos\beta=-2sin(\alpha+\beta)/(2)*sin(\alpha-\beta)/(2)


sin\alpha+sin\beta=2sin(\alpha+\beta)/(2)*cos(\alpha-\beta)/(2)


sin(-\alpha)=-sin(\alpha)\\cos(-\alpha)=cos(\alpha)


(sin\alpha)/(cos\alpha)=tan\alpha

Keeping the above on mind, you can rewrite the expression as following:


=((-2sin(x+3x)/(2)*sin(x-3x)/(2)))/((2sin(x+3x)/(2)*cos(x-3x)/(2)))

Simplify:


=((-2sin(4x)/(2)*sin(-2x)/(2)))/((2sin(4x)/(2)*cos(-2x)/(2)))

(You can cancel out the like terms)


=(-(-sin(2x)/(2)))/(cos(-2x)/(2))\\=(sinx)/(cosx)\\\\=tanx

User Jronny
by
6.3k points